(untitled) (Minerva, 2019)
This study has the goal to examine the Epítome floreado of Caius Iulio Caesar’s Commentarii written in Spanish by the French Carlos de Bonyères, in order to try to determine their sources and their possible links to other commentaries to the Caesareans works. After a deep reading, it can be seen that the aforementioned work is a summary of Casear’s works and that it bears no similarity to other Caesarean commentaries in Spanish, and more specifically to those by Diego Gracián and Gabriel Simeón Florentín, of which they could be considered to be comparable. As the two de Bonyères’ commentaries are based in French originals, the research focuses, on a second stage, in trying to localise the possible French model of the Epítome. Once the model has been found in Henri de Rohan’s work Le parfait Capitaine, the reseach finally focuses in a comparative analysis of both works, both on a general scale (structure) and on a more detail-oriented one (particularities of the text). This research has allowed the authors to identify and verify Rohan’s work as the overarching model of Bonyères’ Epítome, as well as to ascertain the fact that Bonyères used Caesar’s original text when writing his.